EMOTIONAL INTELLIGENCE, WORK-LIFE BALANCE, AND SOCIAL SUPPORT ON HEALTHCARE WORKER PERFORMANCE AT JULOK PUBLIC HEALTH CENTER - Marshanda Aulia Putri; Ibrahim Qamarius; Yanita; Sullaida (CV. Radja Publika, 2026)
This study examines the influence of emotional intelligence, work-life balance, and social support on the performance of healthcare workers at Julok Public Health Center, East Aceh. The research used a quantitative approach with a survey design. The population consisted of 162 healthcare workers, and 62 respondents were selected through simple random sampling based on the Slovin formula. Data were collected using a structured Likert-scale questionnaire and analyzed through validity testing, reliability testing, classical assumption tests, and multiple linear regression using SPSS 26. The findings show that emotional intelligence has a positive and significant effect on healthcare worker performance (B = 0.244; p = 0.003). Work-life balance also has a positive and significant effect (B = 0.439; p = 0.000), while social support has the strongest positive effect (B = 0.472; p = 0.000). The model explains 73.6% of the variance in performance, and the simultaneous test confirms that the three variables jointly affect performance. These results highlight the importance of psychological and social resources in strengthening public health service quality.